2020
DOI: 10.5137/1019-5149.jtn.29771-20.2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic untethering of tight filum terminale: an operative technique

Abstract: AIM: To demonstrate the various technical advantages of minimally invasive endoscopic untethering of tight filum terminale for the treatment of tethered cord syndrome (TCS). MATERIAL and METHODS: In five pediatric cases of TCS, we performed untethering by using the endoscopic technique. The age of the patients were 6, 7, 8, 9, and 12 years old. We used a nasal speculum of the transsphenoidal approach during the endoscopic surgical procedure. RESULTS: All the procedures were performed uneventfully, except for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…An oblique-viewing endoscope is also useful for checking for bleeding or adhesions at the end of the cranially retracted lum terminale. Okay O et al reported that endoscopic release of the lum terminale may provide bene ts such as shorter hospital stay and less blood loss [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An oblique-viewing endoscope is also useful for checking for bleeding or adhesions at the end of the cranially retracted lum terminale. Okay O et al reported that endoscopic release of the lum terminale may provide bene ts such as shorter hospital stay and less blood loss [12].…”
Section: Discussionmentioning
confidence: 99%
“…The classical surgical treatment of lar lipoma is one-level laminectomy or laminectomy and microsurgical sectioning of the lum terminale [8,9]. To keep surgical invasiveness and complications to a minimum, minimally invasive techniques such as the interlaminar approach or endoscopic-assisted techniques have been increasingly used in recent years [5,9,10,11,12]. We present our surgical technique for a minimally invasive full-endoscopic untethering that can be performed through a 1 cm skin incision, the smallest skin incision that has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…An oblique-viewing endoscope is also useful for checking for bleeding or adhesions at the end of the cranially retracted filum terminale. Okay O et al reported that endoscopic release of the filum terminale may provide benefits such as shorter hospital stay and less blood loss [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The classical surgical treatment of filar lipoma is one-level laminectomy or laminectomy and microsurgical sectioning of the filum terminale [ 8 , 9 ]. To keep surgical invasiveness and complications to a minimum, minimally invasive techniques such as the interlaminar approach or endoscopic-assisted techniques have been increasingly used in recent years [ 5 , 9 12 ]. We present our surgical technique for a minimally invasive full-endoscopic untethering that can be performed through a 1 cm skin incision, the smallest skin incision that has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the skin incision was 4-5 cm smaller than that used in conventional techniques, leading to paraspinal muscle dissection and less scar tissue. Okay et al [19] reported a minimally invasive procedure using an endoscopic approach wherein a 2-cm skin incision was used. Greuter et al…”
Section: Literature Report On Minimally Invasive Surgery and Its Comp...mentioning
confidence: 99%